Racial Fault-lines in “Baseball’s Great Experiment:” Black Perceptions, White Reactions - Henry D. Fetter (Transatlantica)
This paper examines three facets of the breaking of major league baseball’s color line by Jackie Robinson of the Brooklyn Dodgers in 1947: the perception of blacks, the response of white players (whether teammates or opponents), and the reaction of baseball fans. By so doing, the paper will illuminate the fault-lines that characterized race relations within both the sport of baseball and the larger society as each was confronted with new challenges to long established policies and practices in the years after the Second World War.